2016
DOI: 10.1159/000448838
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Back Pain and Axial Spondyloarthropathy in Patients with Hidradenitis Suppurativa

Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease, causing fistulating sinuses in the intertriginous skin of axillary, genitofemoral and perianal sites. Objective: As other chronic inflammatory diseases, e.g. psoriasis, are frequently associated with spondyloarthropathies (SpA), the goal of this study was to quantify the prevalence of back pain and SpA in HS patients. Methods: A prospective questionnaire survey in 100 HS patients and a retrospective evaluation of pelvic magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 32 publications
0
46
0
6
Order By: Relevance
“…Earlier studies found that the rate of spondyloarthropathy was significantly higher in HS patients than controls . Comorbid arthritis has been described predominantly in male AAs, which suggests that HS patients may have a genetic predisposition for spondyloarthritis and that inflammatory skin changes induce spondyloarthritis in such patients …”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies found that the rate of spondyloarthropathy was significantly higher in HS patients than controls . Comorbid arthritis has been described predominantly in male AAs, which suggests that HS patients may have a genetic predisposition for spondyloarthritis and that inflammatory skin changes induce spondyloarthritis in such patients …”
Section: Discussionmentioning
confidence: 98%
“…Compared with healthy individuals, patients with HS more often exhibit other autoimmune and autoinflammatory diseases. [99][100][101][102][103][104][105][106][107] The prevalence of inflammatory bowel disease (IBD) in patients with HS is four to eight times higher than the prevalence in the general Northern European population. 104 Notably, Crohn disease and HS occur together at a rate that varies from 0Á6% to 38%.…”
Section: T Helper 17 Cell/regulatory T-cell Axis In Hidradenitis Suppmentioning
confidence: 99%
“…Artikuläre Manifestationsformen zeigen Merkmale einer Spondyloarthritis vom axialen und/oder peripheren Typ [2]. Schätzungen zufolge beträgt die Prävalenz bei HS-Patienten 3,7% bis 48% [3,4]. In den meisten Fällen entwickeln sich die dermatologischen Läsionen vor einer Gelenkbeteiligung.…”
Section: Diskussionunclassified
“…In den meisten Fällen entwickeln sich die dermatologischen Läsionen vor einer Gelenkbeteiligung. Schübe und Schweregrad der Arthritis stehen positiv mit dem Auftreten von HS-Exazerbationen in Korrelation [4]. …”
Section: Diskussionunclassified